Plato's ›Theaetetus‹ Revisited - Bossi, Beatriz; Robinson, Thomas M. (Trends in classics. Supplementary volumes ;, 2020)
This book meets the need to revise the standard interpretations of an apparently aporetic dialogue, full of eloquent silences and tricky suggestions, as it explores, among many other topics, the dramatis personae, including Plato's self-references behind the scene and the role of Socrates on stage, the question of method and refutation and the way dialectics plays a part in the dialogue. More especifically, it contains a set of papers devoted to perception and Plato's criticism of Heraclitus and Protagoras. A section deals with the problem of the relation between knowledge and thinking, including the the aviary model and the possibility of error. It also emphasizes some positive contributions to the classical Platonic doctrines and his philosophy of education. The reception of the dialogue in antiquity and the medieval age closes the analysis. Representing different hermeneutical traditions, prestigious scholars engage with these issues in divergent ways, as they shed new light on a complex controversial work.